HUBUNGAN ANTARA RELIGIUSITAS DAN KECENDERUNGAN MENYAKITI DIRI SENDIRI PADA SISWA YANG BERASAL DARI KELUARGA TUNGGAL - Vidazeya, Mutiara; Firman (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study is motivated by the tendency of self-harm among students from single-parent families. This is evidenced by the increasing divorce rate each year, which is accompanied by a rise in risky behaviors such as self-harm. One of the contributing factors to self-harm among students from single-parent families is a low level of religiosity. Therefore, this study aims to describe the level of religiosity and the tendency of self-harm among these students, as well as to examine and analyze the relationship between religiosity and the tendency of self-harm in students from single-parent families. This research uses a quantitative method with a descriptive correlational research design. The population consists of 50 students from single-parent families enrolled in grades X and XI at SMKN X Padang during the 2024/2025 academic year. The sample includes 23 grade X students from single-parent families, selected using a total sampling technique. Data were collected using a religiosity questionnaire and a self-harm tendency questionnaire for students from single-parent families. The data were analyzed using percentage analysis, and the Pearson product-moment formula was used to test and analyze the relationship between religiosity and the tendency of self- harm. The results showed that students from single-parent families had a moderate level of self-harm tendency, while their level of religiosity was categorized as high. The correlation analysis indicated a negative relationship between religiosity and the tendency of self-harm among students from single- parent families.